1992
DOI: 10.1590/s0004-282x1992000200008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and granulocyte macrophage-csf in the cerebrospinal fluid from hiv infected subjects with involvement of the central nervous system

Abstract: SUMMARY -We detected the cytokines interleukin-6 (IL-6) and granulocyte macrophage-CSF (GM-CSF) by ELISA in the CSF and serum of 30 HIV-infected patients classified as AIDS dementia complex (ADC), and 20 subjects with other neurological diseases (OND). We have found a high incidence of detectable IL-6 and GM-CSF in the CSF of ADC patients compared with OND patients. No statistical differences were observed between both groups for serum IL-6 and GM-CSF levels. These results suggest an intrathecal synthesis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Given the link between HIV disease progression and HAND, these increased CSF cytokines and neurodegenerative biomarkers provide insight into the pathophysiology of HAND. Previous studies have demonstrated higher CSF levels of GM-CSF, TNF-α, MMP-1 and MMP-7 in individuals with HIV-associated dementia and encephalitis as compared with individuals without dementia (Perrella, Guerriero et al 1992, Nottet, Persidsky et al 1996, Conant, McArthur et al 1999). …”
Section: Discussionmentioning
confidence: 95%
“…Given the link between HIV disease progression and HAND, these increased CSF cytokines and neurodegenerative biomarkers provide insight into the pathophysiology of HAND. Previous studies have demonstrated higher CSF levels of GM-CSF, TNF-α, MMP-1 and MMP-7 in individuals with HIV-associated dementia and encephalitis as compared with individuals without dementia (Perrella, Guerriero et al 1992, Nottet, Persidsky et al 1996, Conant, McArthur et al 1999). …”
Section: Discussionmentioning
confidence: 95%
“…Activated astrocytes produce GM-CSF in response to inflammatory signals that would activate microglia, stimulate them to proliferate, and trigger the CNS inflammatory response (41). HIVE is associated with increased GM-CSF production in brains that localized predominantly to astrocytes (15,67), and the AIDS dementia complex is associated with elevated levels of GM-CSF in the cerebrospinal fluid (53). Systemic GM-CSF was reported to induce a 10-fold increase in the HIV load in the spinal fluid of a treated patient (38), and GM-CSF has been reported to increase HIV-1 replication in brain tissue explants (32) and primary monocyte/macrophages and monocyte cell lines (19,37,47,60).…”
Section: Discussionmentioning
confidence: 99%
“…Both M-CSF and GM-CSF are induced in the CNS in response to inflammation, and a growing body of evidence points to a role for these factors in the pathophysiology of brain disease. These CSFs are elevated in the cerebrospinal fluid of patients with Alzheimer's disease (Tarkowski et al, 2001), multiple sclerosis (Carrieri et al, 1998), HIV-associated dementia (Gallo et al, 1994;Perrella et al, 1992), and acute stroke (Tarkowski et al, 1999), and can be produced by a variety of cells within the CNS, including infiltrating and/or perivascular macrophages.…”
Section: Discussionmentioning
confidence: 99%